Quantum-Dot Semiconductor Optical Amplifiers: State Space Model versus Rate Equation Model. (7th March 2013) - Taleb, Hussein; Abedi, Kambiz; Golmohammadi, Saeed
Abstract : A simple and accurate dynamic model for QD-SOAs is proposed. The proposed model is based on the state space theory, where by eliminating the distance dependence of the rate equation model of the QD-SOA; we derive a state space model for the device. A comparison is made between the rate equation model and the state space model under both steady state and transient regimes. Simulation results demonstrate that the derived state space model not only is much simpler and faster than the rate equation model, but also it is as accurate as the rate equation model.